Economic mimicking and social asynchrony of cooperativism in Colombia - Monsalve Z., Alveiro (Cooperativismo & Desarrollo, 2014)
Because cooperativism originated in the midst of an economic and social logic with profound inherentcontradictions —the logic of the capitalist system— it is hard for it to differentiate itself in practice andrationale. The logic of the capitalist model has its own identity, as does the logic of the cooperative mod-el. To exist in practice, however, cooperativism must mimic individualistic and competitive economicpractices within the capitalist system. This situation diminishes the identity and social effectiveness ofcooperativism, and generates asymmetry as an innovative proposal with regard to the socio-economicsof solidarity. This study concludes that to overcome this mimicking and asynchrony, cooperativism musttruly be an autonomous system of sustainable development in the world.
Keywords: cooperativism; social economy; production; socio-economics